Intensifikasi Botanipreneur sebagai Upaya Konservasi Lingkungan pada Siswa Da'watul Khoir Nganjuk - Moch. Faizul Huda; Rossanita Truelovin Hadi Putri; Ospa Pea Yuanita Meishanti; Fatikhatun Nikmatus Sholihah; Anggun Wulandari; Rasyadan Taufiq Probojati (Kadiri University, 2023)
Preserving the environment is a form of love for the environment. Environmental conservation efforts can be carried out through various activities such as botanical exploration and the creation of botanical collections with economic value and their use for economic improvement. The community service activity program is expected to provide knowledge and skills to partners, namely MA Da'watul Khoir, in carrying out botanical exploration techniques and making botanical collections and can increase partner awareness in efforts to preserve the surrounding environment. This service activity also supports conservation measures and efforts to accommodate community needs regarding botanical collections that have economic value. In addition, this service activity also provides knowledge to partners about the introduction of types of trees in the partner school environment that can be used for making botanical collections. This counseling activity contains material on the importance of making botanical collections that have economic value using interactive two-way lecture, discussion and question-and-answer methods. This form of knowledge transfer is not only socialization but also practice. The results obtained from this activity are in the form of an understanding of partners in efforts to explore and conserve botany through the introduction of botanical collections that have economic value. Menjaga kelestarian lingkungan merupakan salah satu bentuk cinta terhadap lingkungan. Upaya konservasi lingkungan dapat dilakukan melalui berbagai kegiatan, seperti eksplorasi botani dan pembuatan koleksi botani yang bernilai ekonomi serta pemanfaatannya dapat meningkatkan perekonomian. Program kegiatan pengabdian kepada masyarakat ini diharapkan mampu memberikan pengetahuan dan keterampilan kepada mitra. Mitra yang dituju ialah MA Da’watul Khoir, mitra tersebut diajarkan dalam melakukan teknik eksplorasi botani dan pembuatan koleksi botani agar dapat meningkatkan kesadaran mitra dalam upaya pelestarian lingkungan di sekitar. Kegiatan pengabdian ini memiliki tujuan dalam menunjang langkah pelestarian dan upaya mengakomodir kebutuhan masyarakat tentang koleksi botani yang bernilai ekonomi. Kegiatan pengabdian ini juga memberikan pengetahuan kepada mitra tentang pengenalan jenis-jenis pohon yang ada di lingkungan sekolah mitra yang dapat digunakan untuk pembuatan koleksi botani. Kegiatan penyuluhan berisi materi tentang pentingnya pembuatan koleksi botani yang bernilai ekonomi menggunakan metode ceramah, diskusi dan tanya jawab yang bersifat interaktif dari dua arah. Bentuk transfer ilmu ini tidak hanya sosialisasi namun juga praktik. Hasil yang didapatkan dari kegiatan ini adalah berupa pemahaman mitra dalam upaya eksplorasi dan konservasi botani melalui pengenalan koleksi botani yang bernilai ekonomi.